(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
The initial spiritual-moral and legal concepts, social perceptions, and skills given to children in the family directly depend on the level of literacy of the parents. In particular, instilling spirituality, ideology, morality, medical culture, and legal concepts into children’s consciousness requires specific knowledge and skills from parents. Based on these tasks, during a seminar-training organized with mothers, we distributed a small questionnaire and monitored their perceptions of family life in general and readiness for it.